TO A QUESTION OF DEVELOPMENT OF THE MAIN DIRECTIONS OF OPTIMUM POLICY OF BANK - A. Zinchenko (Вестник университета)
Article is devoted to problems of efficiency of investments of investment resources and decrease in risks of investors when forming a portfolio of securities. The author has considered economic-mathematical methods of optimization of management of bank activity. The analysis of the expected profitability of security in a problem of formation of the optimum investment portfolio acts as an example of estimation. Results of comparative assessment of the expected profitability of stocks of two companies are given by various methods.